THE USE OF KEY WORD CLUSTERING TO INCREASE STUDENTSâ€™ ABILITY IN WRITING RECOUNT TEXT - Najmuddiyah, Ivana; Salam, Urai; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Â Abstract : This thesis is about how effective key word clustering to improve the studentsâ€™ recount writing. The research is held at SMP Negeri 17 Pontianak in academic year 2013/2014. The writer applied quasi experimental study on her research with one class as the control group and the other class is the experimental group. Â Â Â Â Â Â Â Â Â Â Â From research findings, the mean score of posttest in experimental group was higher than the mean score of posttest in control group (78.3 >54.7). Moreover, the interval of the studentsâ€™ mean score in experimental group was higher than control group (25.1> 0.2). The result of Effect Size was 14.4 (categorized as â€œstrong effectâ€). The t-value (16.27) was bigger than t-table (1.671). The significant difference could be interpreted that the use of key words clustering is effective to improve the studentsâ€™ achievement in writing recount text.Based on the result of the data computation, it was obtained that the t-test score (16.27) was higher than t-table (1.671) at 0.05 the degree of freedom (df)= + -2 (33+33-2=64). This could prove that teaching recount writing by using key words clustering is effective. Keywords : recount, key word clustering, brainstorming Abstrak : Skripsi ini tentang seberapa efektif keyword clustering untuk meningkatkan kemampuan menulis recount siswa. Penelitian ini diadakan di SMP Negeri 17 Pontianak pada tahun akademik 2013/2014. Penulis menerapkan studi eksperimental kuasi pada penelitiannya dengan satu kelas sebagai kelompok kontrol dan kelas lainnya adalah kelompok eksperimen.Â Dari hasil penelitian, nilai rata-rata posttest pada kelompok eksperimen lebih tinggi dari nilai rata-rata posttest kelompok kontrol (78,3> 54,7). Selain itu, interval nilai rata-rata siswa dalam kelompok eksperimen lebih tinggi dibandingkan kelompok kontrol (25,1> 0,2). Hasil Pengaruh Ukuran adalah 14,4 (dikategorikan sebagai